Changing the game: An economy built around stewardship - Prabhu, R.; Colfer, C.J.P. (Routledge, 2023)
This chapter begins by reiterating the calls by the Glassgow Leaders’ Declaration on Forests and Land Use and others for more effective attention to climate change. To respond to these calls, we argue that globally we will need to change ‘the game’ from one based on commodification to one that recognizes the systemic nature of human and natural life and builds a caring economy of stewardship. We then summarize elements of the ACM experiences described in this book that demonstrate the need for better cross-scale collaboration as we seek more enduring transformations than we were able to accomplish by focusing only on the local. We examine some of the history, nature and value of what Prabhu has called a Stewardship Economy in the next section, making the point that both the natural and human elements and related relationships among them need greater attention. We include examples of existing stewardship that emerged ‘in passing’ in the ACM experience, despite the earlier absence of explicit attention to such issues. We conclude with the need to develop mechanisms, such as a ‘stewardship dividend’ to reward those who demonstrate such care.